Knowledge of chemotherapy and occupational safety measures among undergraduate nursing students in Universiti Sains Malaysia (USM) - Shari, Nor Nabila (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Chemotherapy is a cancer treatment that uses drugs that inhibit or slow down the growth of cells for a cancer patient. Cancer has become one of the main health problems as it is one of the most killing diseases in the world. Thus, increasing patients with cancer will also increase the use of chemotherapy drugs for chemotherapy treatment where there will be risk and need more concern about occupational safety measures when handling hazardous drugs. A cross-sectional study was carried out to study the knowledge of chemotherapy and occupational safety measures among undergraduate nursing students in USM. The questionnaire used in this study was self-administered, and it was adopted and adapted from Verstrate (2015) and Nwagbo et. al. (2017). A total of 76 nursing students who fulfilled the inclusion and exclusion criteria were selected randomly. Data collected were statistically analyzed using the SPSS software version 26.0. Fisher’s exact test was used for data analysis. As for the level of knowledge of chemotherapy and occupational safety measures, the results show 45 (59.2%) for good knowledge of chemotherapy and 74 (97.4%) for good knowledge of occupational safety measures respectively. Then the level of awareness results shows 75 (98.7%) with a good level of awareness about prevention measures of chemotherapy and occupational safety measures. Next is there is no association between level of knowledge of chemotherapy and occupational safety measures with selected socio-demographic characteristics (level of education and year of study) (p=0.316), (p=0.805), (p=1.000), and (p=0.553) respectively. In conclusion, the level of knowledge needs to be increased and improved among nursing students as they will be more knowledgeable and skillful in delivering care to chemotherapy patients.